L1 coupling to ankyrin and the spectrin‐actin cytoskeleton modulates ethanol inhibition of L1 adhesion and ethanol teratogenesis. Issue 3 (3rd January 2018) - Dou, Xiaowei; Menkari, Carrie; Mitsuyama, Rei; Foroud, Tatiana; Wetherill, Leah; Hammond, Peter; Suttie, Michael; Chen, Xiaopan; Chen, Shao‐Yu; Charness, Michael E.; Collaborative Initiative on Fetal Alcohol Spectrum Disorders,
Abstract : Ethanol causes fetal alcohol spectrum disorders (FASDs) partly by inhibiting cell adhesion mediated by the L1 neural cell adhesion molecule. Ethanol interacts with an alcohol binding pocket in the L1 extracellular domain (ECD), and dephosphorylation of S1248 in the L1 cytoplasmic domain (CD) renders L1 adhesion insensitive to inhibition by ethanol (L1 insensitive). The mechanism underlying this inside‐out signaling is unknown. Here we show that phosphorylation of the human L1‐CD at S1152, Y1176, S1181, and S1248 renders L1 sensitive to ethanol by promoting L1 coupling with ankyrin‐G and the spectrin‐actin cytoskeleton. Knockdown of ankyrin‐G or L1 mutations that uncouple L1 from ankyrin reduce L1 sensitivity to ethanol, but not methanol, consistent with a small conformational change in the extracellular alcohol binding pocket. Phosphorylation of Y1176 and ankyrin‐G coupling with L1 are higher in NIH/3T3 clonal cell lines in which ethanol inhibits L1 adhesion than in ethanol‐resistant NIH/3T3 clonal cell lines. Similarly, phosphorylation of Y1176 is higher in C57BL/6J mice that are sensitive to ethanol teratogenesis than in ethanol resistant C57BL/6N mice. Finally, polymorphisms in genes that encode ankyrin‐G and p90rsk, a kinase that phosphorylates S1152, are linked to facial dysmorphology in children with heavy prenatal ethanol exposure. These findings indicate that genes that regulate L1 coupling to ankyrin may influence susceptibility to FASD.—Dou, X., Menkari, C., Mitsuyama, R., Foroud, T., Wetherill, L., Hammond, P., Suttie, M., Chen, X., Chen, S.‐Y., Charness, M. E., Collaborative Initiative on Fetal Alcohol Spectrum Disorders. L1 coupling to ankyrin and the spectrin‐actin cytoskeleton modulates ethanol inhibition of L1 adhesion and ethanol teratogenesis. FASEB J. 32, 1364‐1374 (2018). www.fasebj.org